Association Between Epidural Analgesia During Labor and Risk of Autism Spectrum Disorders in Offspring. Issue 3 (March 2021) - Qiu, Chunyuan; Lin, Jane C.; Shi, Jiaxiao M.; Chow, Ting; Desai, Vimal N.; Nguyen, Vu T.; Riewerts, Robert J.; Feldman, R. Klara; Segal, Scott; Xiang, Anny H.
Abstract : (Abstracted from JAMA Pediatr 2020;174(12):1168–1175) More than 70% of pregnant women receive neuraxial anesthesia to manage labor pain in the United States. However, its long-term effects on offspring are largely unknown.